Exchange Rate Pass-Through and International Pricing Strategy: A Conceptual Framework and Research Propositions - Clark, Terry; Kotabe, Masaaki; Rajaratnam, Dan (Journal of International Business Studies, 1999)
The extent to which exchange rate fluctuations affect international prices is called “exchange rate pass-through.” This paper develops a conceptual model in explaining how exchange rate fluctuations are channeled into international pricing strategy, and offers research propositions. Our model posits that the extent of exchange rate pass-through in international pricing is affected by the firm's pricing orientation, performance orientation, distribution policy, and brand equity, as well as by exchange rate uncertainty and competitive symmetry.